Modified Qing’ e Pills exerts anti-osteoporosis effects and prevents bone loss by enhancing type H blood vessel formation - Lu, Junjie; Hu, Desheng; Ma, Chen; Xu, Xiaojuan; Shen, Lin; Rong, Jianhui; Zhao, Jia; Shuai, Bo (Frontiers in Endocrinology, 2022)
Objective: To explore whether the modified Qing’ e Pills (MQEP) exerts anti-osteoporotic effects and prevents bone loss by enhancing angiogenesis. Methods: Network pharmacology was used to assess whether MQEP has a pro-angiogenic capacity and to predict its potential targets. Human umbilical vein endothelial cells were treated with glucocorticoids and MQEP to assess cell viability. The expression of angiotensin II type 1 receptor, angiotensin II type 2 receptor, and angiotensin converting enzyme, which are associated with the activation of the renin-angiotensin-aldosterone system, and the expression of vascular endothelial growth factor and hypoxia-inducible factor 1 alpha, which are associated with the formation of type H blood vessels, were examined by western blot and RT-qPCR. Thereafter, the glucocorticoid-induced osteoporosis model was established and intervened with MQEP. Femur scanning was performed with micro-computed tomography; trabecular spacing, trabecular thickness, and trabecular number were observed and calculated; the expression of nuclear factor-kappa B ligand and osteoprotegerin was detected by ELISA, and the ratio was calculated to evaluate the degree of bone resorption. Finally, type H blood vessels that were highly coupled to osteogenic cells were identified by immunohistochemistry staining and flow cytometry. Results: This is the first study to reveal and confirm that MQEP could prevent bone loss in glucocorticoid-induced osteoporosis by promoting the expression of hypoxia-inducible factor 1 alpha and vascular endothelial growth factor, which are highly associated with type H blood vessel formation. In vitro experiments confirmed that MQEP could effectively promote the proliferation of vascular endothelial cells and alleviate glucocorticoids-induced activation of the renin-angiotensin-aldosterone system, thereby reducing vascular injury. Conclusion: MQEP exerts anti-osteoporosis effects and prevents bone loss by alleviating vascular injury caused by renin-angiotensin-aldosterone system activation and promoting type H blood vessel formation.